2020
DOI: 10.1186/s12935-020-01224-9
|View full text |Cite
|
Sign up to set email alerts
|

TUG1/miR-133b/CXCR4 axis regulates cisplatin resistance in human tongue squamous cell carcinoma

Abstract: Background: Long noncoding RNA taurine upregulated 1 (TUG1) has been reported to play an important role in human cancers. However, little is known about the role of TUG1 in drug resistance and its mechanism in tongue squamous cell carcinoma (TSCC). Methods: Twenty-one cisplatin-sensitive or resistant TSCC patients were enrolled in this study. Cisplatin-resistant cells (SCC25/CDDP and CAL27/CDDP) were used for experiments in vitro. Transfection was performed using Lipofectamine 2000 transfection reagent. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In fact, miR-133 upregulation increases the cisplatin chemosensitivity of cisplatinresistant non small cell lung cancer (NSCLC) cells. Together with TUG1 and CRC4, it is involved in cisplatin resistance even in tongue squamous carcinoma patients [21,22]. Similarly, the findings herein reported, suggest a possible onsuppressive role for miR-133b due to its prominent downregulation in LNEC tissues.…”
Section: Mirnas Clinical Valuesupporting
confidence: 77%
“…In fact, miR-133 upregulation increases the cisplatin chemosensitivity of cisplatinresistant non small cell lung cancer (NSCLC) cells. Together with TUG1 and CRC4, it is involved in cisplatin resistance even in tongue squamous carcinoma patients [21,22]. Similarly, the findings herein reported, suggest a possible onsuppressive role for miR-133b due to its prominent downregulation in LNEC tissues.…”
Section: Mirnas Clinical Valuesupporting
confidence: 77%
“…Wang et al reported that TUG1 facilitated the proliferation, migration and invasion of hepatocellular carcinoma cells through up-regulation of COL1A1 via sequestering miR-29c-3p [40]. A study by Zhang et al showed that depletion of TUG1 abated cisplatin resistance of to ngue squamous cell carcinoma cells via targeting miR-133b/CXCR4 axis [41]. In this study, a negative correlation between TUG1/MSI2 and miR-199a-3p in Ewing's sarcoma patient samples was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Growing lncRNAs have been noted to involve in the initiation and development of several tumours including TSCC. For instance, Zhang et al 35 indicated that TUG1 level was overexpressed in TSCC cells and tissues of cisplatin resistance. Knockdown of TUG1 suppressed cisplatin resistance to CAL27/CDDP and SCC25/CDDP cells via modulating CXCR4 and miR‐133b.…”
Section: Discussionmentioning
confidence: 99%